Lateral vibration control of monopile supported offshore wind turbines with toroidal tuned liquid column dampers. (1st July 2023) - Ding, Hao; Altay, Okyay; Wang, Jin-Ting
Abstract: This study investigates the lateral vibration control efficiency of toroidal tuned liquid column dampers (TTLCDs) for monopile supported offshore wind turbines. The TTLCD has the advantage that it can be tuned to match the natural frequencies of wind turbines both in fore-aft and side–side directions simultaneously. A general mathematical modeling of the TTLCD inside the nacelle is derived and an interface between the simulation platforms MATLAB/Simulink and FAST is established. A TTLCD design procedure is provided for monopile wind turbines. Numerical calculations are carried out for different wind velocities, wave-wind misalignment angles and working conditions considering fatigue and ultimate load cases. A parametric analysis is performed on the flow resistance coefficient of TTLCDs. The results demonstrate that TTLCDs can effectively control lateral vibrations and improve the structural performance of monopile wind turbines against wind and wave loads. Graphical abstract: Highlights: A toroidal tuned liquid column damper (TTLCD) is designed for wind turbines. An analytical model of the TTLCD attached to wind turbine nacelle is derived. The TTLCD model is coupled with the wind turbine simulation tool FAST v8. Various wave and wind load cases are analyzed comprehensively. The TTLCD is valid for bidirectional vibration control of monopile wind turbines.